System-Level Barriers to End-of-Life Care Integration in Critical Care Units: A Cross-Sectional Study Informing Anaesthesia-Led Interventions - Acharya, Krishna Prasad; Pandey, Alisha; Shrestha, Ava (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: End-of-Life Care (EOLC) is given to patients until their final days and hours of life. Nurses’ knowledge and attitudes play an essential role in delivering successful and efficient EOLC. Framed within intensive care contexts, this study uses nurse-level knowledge and attitude as proxy indicators of organisational readiness and system-level barriers to integrating EOLC in intensive care units (ICUs) and high-dependency units (HDUs), with implications for anaesthesia-led interventions. Methods: In July 2024, a cross-sectional study was carried out among 124 nurses selected via non-probability proportionate quota sampling from Bir Hospital and National Trauma Center. A self-administered structured questionnaire assessed knowledge and attitude towards end-of-life care. Chi-square tests examined associations of knowledge and attitude with selected variables, and Spearman’s rank correlation assessed the correlation between knowledge and attitude. Results: The highest proportion (37.9%) of participants had a moderate level of knowledge, and most (88.7%) had a positive attitude regarding end-of-life care, with mean scores of 24.47 ± 7.487 and 106.14 ± 17.788, respectively. Knowledge showed associations with working experience, hospital, and training; attitude showed an association with ethnicity. Knowledge and attitude were weakly correlated (r = 0.274, p = 0.002). Taken together, limited formal training and institution-related differences indicate system-level barriers to consistent EOLC integration in critical care units. Conclusion: While most nurses demonstrated positive attitudes, the predominance of only moderate knowledge and the dependence of knowledge on training and institutional context point to organisational gaps that impede EOLC integration. The study highlights the need to integrate EOLC into curricula and to conduct educational interventions and training enabling nurses to deliver EOLC effectively. These results provide actionable, system-level insights for anaesthesia-led strategies, such as ICU protocol development, interdisciplinary training, and workflow integration, to embed EOLC within critical care.